Os espaços de participação e de exercício da cidadania, na voz de líderes associativos da província de Cabo Delgado - Feijó, João (Observador Rural, 2023)
O texto descreve os obstáculos históricos ao desenvolvimento de organizações da sociedade civil (OSC) em Moçambique, que conheceram um cenário mais acolhedor na Constituição de 1990. Mecanismos de apoio à sociedade civil capacitaram líderes locais, tornando-os melhor conhecedores de dispositivos legais, capazes de reunir evidências e de exercer impacto junto das populações. Contudo, as organizações enfrentaram problemas internos, relacionados com a ausência de recursos financeiros, com a capacitação dos seus membros e com problemas de transparência e rotatividade. O sistema de ensino desenvolve poucas competências de cidadania activa e o Estado desconfia de iniciativas de consciencialização das populações em direitos fundamentais ou em mecanismos de participação cívica. A manutenção de uma cultura política de súbdito foi funcional à penetração do grande capital na exploração de recursos naturais. As OSC enfrentam obstáculos à participação, relacionados com a forte politização da sociedade, com a desconfiança governamental em relação ao escrutínio público, proibição de manifestações públicas e receio das suas lideranças, particularmente após o início do conflito armado. A proliferação de conflitos nas áreas da indústria extractiva e a inexistência de canais formais de participação e de acesso à justiça foram agudizaram tensões, habilmente capitalizadas por grupos violentos. A guerra dispersou os membros de OSC que timidamente floresciam nos vários distritos, retirando-lhes capacidade organizativa, de advocacia e pressão social. A chegada de organizações humanitárias internacionais em resposta à emergência pouco incluiu as associações locais, reproduzindo relações assistencialistas e de dependência. O texto demonstra a urgência de identificação de líderes locais, (re)capacitação das OSC e criação de fóruns de participação social, invertendo a crença de que a violência constitui a forma possível e legítima de participação.
Keywords: *tagged; G - Mozambique / Moçambique; GP - Cabo Delgado; L - portuguese / português; authority / autoridade; citizenship & participation / cidadania e participação; civil society / sociedade civil; conflict / conflito; extractive industries / indústrias extractivas; governance / governação

Spaces for participation and exercise of citizenship, in the voice of associative leaders in the province of Cabo Delgado - Feijó, João (Observador Rural, 2023)
The text describes the historical obstacles to the development of civil society organizations (CSOs) in Mozambique, which experienced a more welcoming scenario in the 1990 Constitution. Mechanisms to support civil society empowered local leaders, making them better knowledgeable of legal provisions, capable of gathering evidence and making an impact on the population. However, the organizations faced internal problems, related to the lack of financial resources, the training of their members and problems of transparency and turnover. The education system develops few competencies of active citizenship, and the State is distrustful of initiatives to raise the awareness of the populations on fundamental rights or on mechanisms of civic participation. The maintenance of a political culture of subject has been functional to the penetration of big capital in the exploitation of natural resources. CSOs face obstacles to participation, related to the strong politicization of society, government distrust of public scrutiny, prohibition of public demonstrations and fear of their leadership, particularly after the beginning of the armed conflict. The spread of conflicts in extractive industry areas and the absence of formal channels for participation and access to justice intensified tensions, which were skilfully capitalized on by violent groups. The war dispersed the members of CSOs that were timidly flourishing in the various districts, taking away their organizational, advocacy and social pressure capacity. The arrival of international humanitarian organisations in response to the emergency included local associations, reproducing relations of assistance and dependency. The text demonstrates the urgency of identifying local leaders, (re)empowering CSOs and creating forums for social participation, reversing the belief that violence constitutes the possible and legitimate form of participation.
Keywords: *tagged; G - Mozambique / Moçambique; GP - Cabo Delgado; L - english / inglês; citizenship & participation / cidadania e participação; civil society / sociedade civil; conflict / conflito; extractive industries / indústrias extractivas; security / segurança

Estabelecimento Da Rede Moçambicana dos Defensores de Direitos Humanos (RMDDH) Nas Províncias de Tete, Gaza, Nampula - RMDDH (CDD - Centro para Democracia e Desenvolvimento Mozambique, 2021)
A Rede Moçambicana dos Defensores de Direitos Humanos (RMDDH) está a levar a cabo actividades de identificação e mapeamento de defensores de direitos humanos nas províncias, que incluem pessoas singulares e organizações da sociedade civil que estão na linha de frente na luta pela defesa dos direitos humanos. Financiado pela OCISA, o trabalho iniciou em Abril último na Província de Tete, centro de Moçambique, onde a RMDDH realizou vários encontros com organizações da sociedade civil que trabalham na área dos direitos humanos e com instituições governamentais e estatais
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Gaza; GP - Nampula; GP - Tete; L - portuguese / português; civil society / sociedade civil

Niassa: MASC desencoraja envolvimento de jovens nos ataques terroristas - User, Super (2020)
A Fundação MASC - Mecanismo de Apoio a Sociedade Civil, no Niassa, desencoraja o envolvimento de jovens nos ataques terroristas na vizinha província d...
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - portuguese / português; civil society / sociedade civil; conflict / conflito; youth / juventude

Narrativas Alternativas: Lançamento Do Álbum Moçambique Yethu! #stopviolenciaextremista - MASC, Fundação (Fundação MASC, 2020)
Desde o final de 2017, Cabo Delgado, tem sido palco de violentos ataques de grupos […]
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; civil society / sociedade civil; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; youth / juventude

Representation and Inclusion in School Councils in Mozambique - Taela, Kátia; López Franco, Erika; Alex, Shankland; Maivasse, Catija; Chilengue, Nárcya; Goodfry, Claudino (Institute of Development Studies, 2018)
This study was conducted as part of the Citizen Engagement Programme (Programa Cidadania e Participação (CEP)) in Mozambique – an empowerment and social accountability initiative to improve the quality of education and health services by increasing citizens’ influence on the management of schools and health units, the formulation of education and health policies, and the provision of education and health services. In education, CEP enabled citizen monitoring of services through the community scorecard (Cartão de Pontuação Comunitária (CPC)), focusing on the link between CPC action plans and the work plans of the co-management mechanism in schools – the school councils. CEP has also promoted the channelling of issues beyond the capacity and mandate of schools to higher levels of the national education system. This work identified a need to better understand the role of school councils as a link between the school and the community, and also in escalating important matters to higher levels of management in the education system, beyond that of school authorities. It was in this context that the Institute of Development Studies and the Centre for Learning and Capacity Building for Civil Society, both members of the CEP consortium, proposed to undertake a qualitative study on representation and inclusion in school councils. The primary aim of this study was to widen the knowledge base available to civil society and to government on the factors that contribute to good performance by school councils in building inclusivity and social accountability to improve the quality of education services.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; Important; L - english / inglês; M - ethnography / etnografia; access to services / acesso a serviços; citizenship & participation / cidadania e participação; civil society / sociedade civil; decentralization / descentralização; education / educação; health / saúde; social inclusion & exclusion / inclusão e exclusão social

Civil society organisations’ political control over Brazil and Japan’s development cooperation in Mozambique: More than a mere whim? - Chichava, Sérgio; Durán, Jimena (LSE Global South Unit, 2016)
This article aims to analyse and explain the reasons behind the CSOs’ strong criticism of the ProSavana programme. This will contribute toward: (1) understanding the role of Mozambican CSOs as actors regulating international development cooperation projects; (2) revealing the political and economic interests behind ProSavana, as a first step toward a more critical approach to trilateral cooperation; and (3) illustrating through this case how a partnership between Brazil and “traditional” donors actually works. Firstly, we will analyse the cooperation policies of Brazil and Japan in Mozambique, taking into account its evolution, actors, mechanisms and motives. Secondly, we will introduce ProSavana, examining the narratives and roles of Japan and Brazil in this programme. Thirdly, we will consider the engagement of CSOs from the three countries, their role in exerting a political check on the Brazilian and Japanese governments, investors, and companies, as well as their narratives and mechanisms of protest.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; civil society / sociedade civil; development partners / parceiros de cooperação